Efficacy of epidermal growth factor tocotrienol rich fraction cream formulation in deep-partial thickness burn in Sprague-Dawley rats - Ahmad Zaini, Asma (2018)
Silver Sulfadiazine (SSD) is primarily used as a topical burn treatment. However, it has been reported that SSD cream can cause adverse reactions like allergy and toxicity. Thus, in this study the burn healing properties of epidermal growth factor (EGF) and tocotrienol rich fraction (TRF) formulation were evaluated. This study was conducted in four stages. The first and second stages were to evaluate the efficacy of TRF (3-5%) and EGF (A-C%) separately, meanwhile the third stage was to study the synergistic effect of both compounds in burn wound healing. Sprague-Dawley male rats were divided into 6 groups (n=7). The deep-partial thickness burn wounds were performed on the shaved skin with the exposure to 100°C heat for 10 second. Treatment was applied topically once daily to the burned areas for 21 days. The measurable outcomes involved rate of wound contraction, clinical evaluation, H&E staining and cellular population number. The results were analyzed for statistical significance using two-way ANOVA for microscopic study and two way repeated measure for macroscopic study. Bonferonni test was performed for the significant treatment means. The optimum dosage of both ingredients obtained was further used for the formulation of EGF-TRF cream and the synergistic effects were determined. TRF at 3% concentration showed most advanced healing indicated with better cosmetic and histopathological outcome, highest percentage of wound contraction rate at day 5, 9, 13, and 17 with 43.34±2.13, 62.87±1.74, 92.38±2.48 and 100.00±0.00 respectively, lowest count of neutrophils and macrophages. The highest dose (C%) of EGF increased the healing process indicated with better cosmetic and histopathological outcome and highest percentage of wound contraction rate at day 13 and 17 with 78.82±2.40 and 100.00±0.00 respectively. Hence, for the third stage study, A-C% EGF were mixed with 3% TRF. The best formulation was further used in the fourth stage. Microscopic changes of the collagen in the dermal layer for the optimum formulation (C% EGF + 3% TRF) was monitored. Current finding demonstrated the C% EGF + 3% TRF treatment exhibited excellent gross appearance, highest percentage of wound contraction rate in all experimental period and full histological score as early as day 14. Microscopic evaluation demonstrated that there was a significant acceleration of the epidermal and dermal repair in C% EGF + 3% TRF. Collagen staining also showed increased fibroblast proliferation and collagen synthesis in C% EGF + 3% TRF. Combination of C% EGF + 3% TRF exhibited synergistic effects with better potential than the effects of these two compounds alone in accelerating burn wound healing. In addition, combination of EGF and TRF treatments showed better healing ability as compared to SSD. In conclusion EGF-TRF formulation is capable to accelerate the burn wound healing with better cosmetic outcome in the deep-partial thickness burn on various phase of burn wound healing.